Persepsi Pengguna Layanan Pengadaan Barang dan Jasa pada Pemerintah Kota Yogyakarta terhadap Implementasi Sistem E Procurement - Ita Akyuna Nightisabha; Djoko Suhardjanto; Bayu Tri Cahya (Jurnal Siasat Bisnis, 2009)
This study aims to evaluate the implementation of electronic procurement of goods and services by the Government City of Yogyakarta, as an effort to create good governance especially in terms of procurement. This study compares the perceptions of user that consist of procurement committee and the providers of goods and services. Research location is in Layanan Pengadaan Secara Elektronik (LPSE) of Government City of Yogyakarta as a system developer with the sample of the procurement committee and partner of goods and services that are spread in Yogyakarta and surrounding areas. This research uses t-test by using a reference measurement system on the success of end-user computing satisfaction developed by Torzadeh and Doll (1991). The results show a difference of perception between the committee and the procurement of goods and services providers to the implementation of e-proc system. There is difference in perception between users of e-procurement supplier of goods / services and the procurement committee. Implementation of e-procurement system is being run by the Government City of Yogyakarta is currently has not been relatively applied, because the technology gap that has led to the differences in perception between the committee and the procurement of goods and services providers.Keywords: good governance, e-procurement, perception